2019
DOI: 10.1111/hsc.12806
|View full text |Cite
|
Sign up to set email alerts
|

“Keeping Control”: A user‐led exploratory study of mental health service user experiences of targeted violence and abuse in the context of adult safeguarding in England

Abstract: The situation for people with mental health problems as a group of disabled people who experience targeted violence and abuse is a complex one. Disabled people, particularly those with mental health problems, are at higher risk of targeted violence and hostility with few effective evidence‐based prevention and protection strategies. Achieving effective safeguarding for adults with mental health problems is characterised by differential attitudes to and understandings of abuse by safeguarding practitioners, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…where some of the basic premises of professional knowledge are strongly contested, as in mental health where the biomedical model is widely disputed. 34,35 Beresford 36 and Russo 30 challenge the assumption underlying positivist research that the greater the distance from the experience under investigation, the more reliable the view: 1 Note: because of the study focus on adult safeguarding, we use the term 'targeted violence and abuse'.…”
Section: Experiential Knowledge Has a Significant Contribution To Makementioning
confidence: 99%
See 3 more Smart Citations
“…where some of the basic premises of professional knowledge are strongly contested, as in mental health where the biomedical model is widely disputed. 34,35 Beresford 36 and Russo 30 challenge the assumption underlying positivist research that the greater the distance from the experience under investigation, the more reliable the view: 1 Note: because of the study focus on adult safeguarding, we use the term 'targeted violence and abuse'.…”
Section: Experiential Knowledge Has a Significant Contribution To Makementioning
confidence: 99%
“…The study findings are reported in detail elsewhere. 1 A summary of the key findings is given below:…”
Section: K E Y Find Ing S From the Main S Tu Dymentioning
confidence: 99%
See 2 more Smart Citations
“…Guidelines on co‐production have been developed based on different implementation experiences (Carr et al . ). Cost‐effectiveness, health benefits, prevention, improvement of practical skills, and social capital are considered the strengths of co‐production experiences (Needham & Carr ).…”
Section: Introductionmentioning
confidence: 97%